IMPLEMENTASI ALGORITMA HAVERSINE UNTUK PERHITUNGAN JARAK ANTARA LOKASI PERUSAHAAN DENGAN KARYAWAN PADA PT MEGA GIGA SOLUSIND - Luthfia Nur Aini; Endah Tri Esti Handayani; Rini Nuraini (Journal of Research and Publication Innovation, 2024)
Luthfia Nur Aini, 227064426164, Informatics Study Program. The use of mobile devices has significantly expanded in Indonesia, including in employee attendance systems. However, many companies still rely on manual attendance methods, such as fingerprint systems, which present several drawbacks, particularly in supporting remote work and operational efficiency. This study aims to develop a mobile attendance application using the Haversine algorithm to calculate the distance between employees' locations and the office at PT Mega Giga Solusindo. The Haversine algorithm is employed to ensure accurate distance calculation based on geographical coordinates, facilitating automated and real-time attendance tracking. This application is expected to address the challenges of manual attendance and enhance the company's operational efficiency. The research methodology involves software development using the Agile approach, and the application is tested through blackbox testing to ensure its functionality.